Specific surface area of titanium dioxide (TiO2) particles influences cyto- and photo-toxicity - Xiong, Sijing (2013)
The aim of this study is to examine how different specific surface areas of similar-sized titanium dioxide (TiO2) particles could influence both cytotoxicity and phototoxicity. TiO2 particles of different specific surface areas were compared for their toxic effects on RAW264.7 cells in the absence and presence of UV light. From the results, TiO2 particles with larger specific surface area were found to induce higher cyto- (UV absent) and photo-toxicity (UV activated) to cells after 24 h incubation. The observed cytotoxicity from TiO2 particles with larger surface area could be explained from their interactions with biomolecules. Upon photoactivation, a larger number of hydroxyl radicals were detected from TiO2 particles with larger surface area, again suggesting a surface area dependent phototoxic effect. On the other hand, pre-adsorbing TiO2 particles with extracellular proteins were found to decrease toxicity effects.